High-dose vitamin C treatment reduces capillary leakage after burn plasma transfer in rats - Kremer, Thomas; Harenberg, Patrick; Hernekamp, Jochen-Frederick; Riedel, Katrin; Gebhard, Martha-Maria; Germann, Günter; Heitmann, Christoph; Walther, Andreas (Journal of burn care & research, 2010)
Oxidative stress after burn injuries leads to systemic capillary leakage and leukocyte activation. This study evaluates whether antioxidative treatment with high-dose vitamin C leads to burn edema reduction and prevention of leukocyte activation after burn plasma transfer. Donor rats underwent a burn (n = 7; 100°C water, 12 seconds, 30% body surface area) or sham burn (37°C water; n = 2) procedure and were killed after 4 hours for plasma harvest. This plasma was administered to study rats (continuous infusion). Rats were randomized to four groups (n = 8 each; burn plasma alone [BP]; burn plasma/vitamin C-bolus 66 mg/kg and maintenance dose 33 mg/kg/hr [VC66]; burn plasma/vitamin C-bolus 33 mg/kg and maintenance dose 17.5 mg/kg/hr [VC33]; and sham burn plasma [SB]). Intravital fluorescence microscopy in the mesentery was performed at 0, 60, and 120 minutes for microhemodynamic parameters, leukocyte adherence, and fluorescein isothiocyanate-albumin extravasation. No differences were observed in microhemodynamics at any time. Burn plasma induced capillary leakage, which was significantly higher compared with sham burn controls (P < .001). VC66 treatment reduced microvascular barrier dysfunction to sham burn levels, whereas VC33 had no significant effect. Leukocyte sticking increased after burn plasma infusion, which was not found for sham burn. Vitamin C treatment did not influence leukocyte activation (P > .05). Burn plasma transfer leads to systemic capillary leakage. High-dose vitamin C treatment (bolus 66 mg/kg and maintenance dose 33 mg/kg/hr) reduces endothelial damage to sham burn levels, whereas half the dose is inefficient. Leukocyte activation is not influenced by antioxidative treatment. Therefore, capillary leakage seems to be independent from leukocyte-endothelial interactions after burn plasma transfer. High-dose vitamin C should be considered for parenteral treatment in every burn patient.